2014
DOI: 10.4028/www.scientific.net/msf.798-799.21
|View full text |Cite
|
Sign up to set email alerts
|

Purified Smectite Clays Organofilized with Ionic Surfactant for Use in Oil-Based Drilling Fluids

Abstract: The main bentonite reservs in Brazil are located in Boa Vista, PB. In order on widening the reserves, on the mineral production and on the consolidation of the state as the largest producer in the country, many studies have been carried out by UFCG on the clays recently discovered in the Districts of Cubati and Pedra Lavrada. This work is intended for the characterization of new deposits, for the development of natural and organofilic clays, which will be employed in oil-based drilling fluids. The characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
1
5
0
2
Order By: Relevance
“…These results showed that the clay used in this study had elevated levels of accessory minerals such as kaolinite, mica, quartz, feldspar and calcite. These results are similar to preliminary results found in [19]. Fig.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…These results showed that the clay used in this study had elevated levels of accessory minerals such as kaolinite, mica, quartz, feldspar and calcite. These results are similar to preliminary results found in [19]. Fig.…”
Section: Methodssupporting
confidence: 83%
“…As they do not have moving parts, hydrocyclones require low investment in installation and maintenance and are simple to operate, being widely used in the chemical, mineral, textile and petrochemical industries. Some studies using hydrocyclone for the treatment of minerals have been highlighted in recent years, among them the works [9][10][11][12][13][14][15][16][17][18][19][20][21]. These studies concluded that this type of equipment has high efficiency in the separation of fine and coarse particles, with easy operation requiring low investment for installation and maintenance, and having relevant importance in the treatment of non-metallic minerals.…”
Section: Factorial Design and Statistical Analysis Of Smectite Clay Tmentioning
confidence: 99%
“…A simple method for purification of clay was analyzed, with tests showing that centrifuge speed influences the purification process of bentonite; low speeds reduce the purification level and high speeds reduce the performance of montmorillonite [21]. Research studies involving the purification of clay by the hydrocyclone method have been developed at the Federal University of Campina Grande (UFCG), with special mention of [22][23][24][25][26], in which the efficiency of this method was confirmed for several different applications.…”
Section: Influence Of the Purification Of Bentonite Clay From New Depmentioning
confidence: 99%
“…As variedades comercializadas atualmente apresentam um elevado grau de contaminação por minerais acessórios, como quartzo, feldspato, gipsita, albita, halita, calcita, pirita, carbonatos de sódio e outros, que por vez comprometem suas aplicações tecnológicas [6]. Alguns estudos com objetivo de eliminar esses minerais acessórios têm sido desenvolvidos nos últimos anos com destaque o trabalho [7], que utilizou a técnica da hidrociclonagem [7][8][9][10].…”
Section: Introductionunclassified